Characterization and Antibacterial Activity Test of Green Synthetic ZnO Nanoparticles Using Avocado (Persea americana) Seed Extract - Nanda Saridewi; Adelian Risa Adinda; Siti Nurbayti (Jurnal Kimia Sains dan Aplikasi, 2022)
The ability of cotton fabrics to absorb water creates several problems, such as providing an environment for bacterial growth. Antibacterial properties of textiles can be conducted by coating with nanoparticles with antibacterial activity. This study aimed to synthesize ZnO via green process nanoparticles using avocado seed extract (Persea americana), then characterize and evaluate its antibacterial activity on cotton fabrics. This research began with extracting avocado seed powder with distilled water. Then the avocado seed extract was mixed with Zn(CH3COO)2.2H2O and heated in a water bath at 70°C. The mixture was stirred while NaOH was added until the mixture reached pH 7, 8, and 9. The FTIR measurement of the avocado seed extract showed the presence of free hydroxyl and amino groups that act as reducing agents, capping agents, and stabilizers in the synthesis of ZnO nanoparticles. The XRD pattern of synthesized ZnO nanoparticles was hexagonal. The SEM results showed that the morphology of ZnO nanoparticles was spherical, with a particle size of 19.965 nm. Antibacterial activity was carried out on the cotton cloth coated with ZnO nanoparticles, resulting in an inhibition zone of 1.8 cm against E. coli and 1.97 cm against S. aureus bacteria. This study result indicated that ZnO nanoparticles have antibacterial activity by producing inhibition against E. coli and S. aureus.